Situating the salience and parietal memory networks in the context of multiple parallel distributed networks using precision functional mapping - Young Hye Kwon; Joseph J. Salvo; Nathan L. Anderson; Donnisa Edmonds; Ania M. Holubecki; Maya Lakshman; Kwangsun Yoo; B.T. Thomas Yeo; Kendrick Kay; Caterina Gratton; Rodrigo M. Braga (Cell Reports)
Summary: Brain networks serving higher cognitive functions are widely distributed across frontal and posterior association zones. Two exceptions have been the parietal memory network (PMN) and salience network (SAL), which are typically restricted to posterior (e.g., posterior cingulate and lateral parietal cortex) and anterior (medial prefrontal and anterior insular cortex) areas, respectively. Using high-resolution neuroimaging, we show that individualized estimates of the PMN extend beyond the posterior set and encompass frontal and insula regions canonically ascribed to the SAL. This suggests that the SAL and PMN form a unified network: “SAL/PMN.” Task-based analyses confirm that both anterior and posterior components of the SAL/PMN show recognition-related activity. Comparison of 3T and 7T data suggests that high-resolution data more readily revealed the unified network, underscoring the importance of fine-scale distinctions for veridical representation of brain networks. Importantly, the unified network better matches the expected parallel distributed network organization that is characteristic of association cortex.